Clinical Features and Genetic Risk of Demyelination Following Anti-TNF Treatment. (4th May 2020) - Lin, Simeng; Green, Harry D; Hendy, Peter; Heerasing, Neel M; Chanchlani, Neil; Hamilton, Benjamin; Walker, Gareth J; Heap, Graham A; Hobart, Jeremy; Martin, Roswell J; Coles, Alasdair J; Silverberg, Mark S; et al.
Abstract: Background: Anti-TNF exposure has been linked to demyelination events. We sought to describe the clinical features of demyelination events following anti-TNF treatment and to test whether affected patients were genetically predisposed to multiple sclerosis [MS]. Methods: We conducted a case-control study to describe the clinical features of demyelination events following anti-TNF exposure. We compared genetic risk scores [GRS], calculated using carriage of 43 susceptibility loci for MS, in 48 cases with 1219 patients exposed to anti-TNF who did not develop demyelination. Results: Overall, 39 [74%] cases were female. The median age [range] of patients at time of demyelination was 41.5 years [20.7–63.2]. The median duration of anti-TNF treatment was 21.3 months [0.5-99.4] and 19 [36%] patients were receiving concomitant immunomodulators. Most patients had central demyelination affecting the brain, spinal cord, or both. Complete recovery was reported in 12 [23%] patients after a median time of 6.8 months [0.1–28.7]. After 33.0 months of follow-up, partial recovery was observed in 29 [55%] patients, relapsing and remitting episodes in nine [17%], progressive symptoms in three [6%]: two [4%] patients were diagnosed with MS. There was no significant difference between MS GRS scores in cases (mean -3.5 × 10 –4, standard deviation [SD] 0.0039) and controls [mean -1.1 × 10 –3, SD 0.0042] [ p = 0.23]. Conclusions: Patients who experienced demyelination events following anti-TNF exposure were more likely female, less frequently treated with an immunomodulator, and had a similar genetic risk to anti-TNF exposed controls who did not experience demyelination events. Large prospective studies with pre-treatment neuroimaging are required to identify genetic susceptibility loci.